2015
DOI: 10.1080/15384047.2015.1071731
|View full text |Cite|
|
Sign up to set email alerts
|

Bisindole-PBD regulates breast cancer cell proliferation via SIRT-p53 axis

Abstract: In a previous study we reported the role of potent bisindole-PBD conjugate as an inclusion in the arsenal of breast cancer therapeutics. In breast cancer cell proliferation, PI3K/AKT/mTOR pathway plays a crucial role by prosurvival mechanism that inhibits programmed cell death. Here, 2 breast cancer cells lines, MCF-7 and MDA-MB-231 were treated with Vorinostat (suberoylanilide hydroxamic acid / SAHA) and bisindole-PBD (5b). We have investigated the effect on PI3K/AKT/mTOR pathway and SIRT expression including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Ablation Akt activity could reverse high proliferation ability mediated by SIRT1. These results commonly revealed intricate connections between SIRT1 and Akt which demonstrated that the SIRT1/Akt signaling axis could significantly affect the development of breast cancer, suggesting its meaningful status in breast cancer diagnosis and treatment 29 - 31 .…”
Section: Discussionmentioning
confidence: 85%
“…Ablation Akt activity could reverse high proliferation ability mediated by SIRT1. These results commonly revealed intricate connections between SIRT1 and Akt which demonstrated that the SIRT1/Akt signaling axis could significantly affect the development of breast cancer, suggesting its meaningful status in breast cancer diagnosis and treatment 29 - 31 .…”
Section: Discussionmentioning
confidence: 85%
“…While the functional roles of most of the lncRNAs in the co-expression network have not been previously studied, the mRNAs that have co-expression relationship with those lncRNAs have been previously reported to have important roles in various tumors including prostate cancer, glioma, breast cancer and squamous cell carcinoma of the lung (39, 44-45). Therefore, according to the functional roles of these mRNAs, we could prioritize the lncRNAs that might play key roles in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Since p53 and NAD are both proved to influence the energy metabolism in cancer cells and the acetylation of p53 is regulated by NAD-dependent SIRT1 deacetylase [ 9 , 25 ], the NAD metabolism may be potentially linked with p53 function in CRC tissues. As a tumor suppressor, p53 is frequently mutated in various neoplastic types during tumorigenesis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinamide mononucleotide adenylyl transferases (NMNATs) are rate-limiting enzymes, which catalyze the synthesis of NAD from nicotinamide mononucleotide (NMN). Three NMNAT isoforms have been identified in mammals, including NMNAT1, NMNAT2, and NMNAT3 [ 4 , 9 ]. Among the three NMNAT isoforms, NMNAT2 is reported to be most sensitive to NAD and can act as a sensor to intracellular metabolic state and high levels of NMNAT2 were detected in the organs with high energy consumption, such as heart, brain, and skeletal muscle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%